2022
DOI: 10.21037/atm-22-401
|View full text |Cite
|
Sign up to set email alerts
|

Application and thinking of minimally invasive transforaminal lumbar interbody fusion in degenerative lumbar diseases

Abstract: Background: This study sought to investigate the clinical efficacy and safety of minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in the treatment of lumbar degenerative diseases. Methods: The clinical data of 55 patients with lumbar degenerative diseases treated at our hospital from January 2018 to January 2020 were analyzed retrospectively. Of the 55 patients, 35 who underwent MIS-TLIF were included in the MIS-TLIF group, and 20 who underwent posterior lumbar interbody fusion (PLIF) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Many studies have shown that MIS-TLIF has a longer operative time than open surgery, which is attributed to the steep learning curve of MIS-TLIF and the need for additional intraoperative fluoroscopy to optimize the position of the pedicle screws [ 13 , 14 ]. Price et al investigated 452 patients who underwent TLIF surgery and reported that the MIS-TLIF procedure time was significantly lower than that of TLIF [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that MIS-TLIF has a longer operative time than open surgery, which is attributed to the steep learning curve of MIS-TLIF and the need for additional intraoperative fluoroscopy to optimize the position of the pedicle screws [ 13 , 14 ]. Price et al investigated 452 patients who underwent TLIF surgery and reported that the MIS-TLIF procedure time was significantly lower than that of TLIF [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The minimally invasive spine surgery innovation and advanced devices promote the minimally invasive TLIF in LDH. 20 , 21 Thus, Foley et al . first proposed minimally invasive TLIF aiming to reduce and avoid intraoperative multifidus stripping and stretching.…”
Section: Introductionmentioning
confidence: 99%
“…The minimally invasive spine surgery innovation and advanced devices promote the minimally invasive TLIF in LDH 20,21 . Thus, Foley et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation